Empowerment of Elementary School Teachers 193 Caringin in the implementation of digital-based literature learning media as an effort to improve students' morals and love for national culture [Pemberdayaan Guru SDN 193 Caringin dalam implementasi media pembelajaran sastra sebagai upaya meningkatkan akhlak dan kecintaan siswa terhadap budaya bangsa] - Pratikno, Heru; Rosenda, Diden; Baksin, Askurifai (Universitas Syiah Kuala, 2025)
Good and polite language skills for elementary school students are now starting to decline. They feel proud and dominant in using rude, dirty, and even hurtful language to their friends. If left unchecked, these bad morals will actually cause social conflict and become legal problems in the future. Of course, such problems will have a negative impact on the golden generation because they are starting to lose their humanistic national cultural identity. Not only that, the performance of teachers in teaching language and literature to students is also less creative so that it makes students feel bored to learn about Indonesian literature. In fact, literature is able to make their human resources superior and have character. Therefore, the role of strong teachers is needed in teaching and educating students related to learning Indonesian literature. One of the efforts is that teachers need to teach students using fun literary learning media. Therefore, the purpose of this community service is to provide an introduction and description to elementary school teachers about what unique language and literature learning media are. With this community service, teachers are given an understanding of the concept, type, benefits, and use of learning media. Then, another goal of this community service is that teachers are taught how to create unique and innovative literary learning media through AI computerized design. Thus, teachers can implement the learning media in SDN 193 Caringin. Of course, with the hope that it will arise in students' love for the language, literature, and culture of the archipelago.